Mossy fiber expression of αSMA in human hippocampus and its relevance to brain evolution and neuronal development - Tian Tu; Xiao-Lu Cai; Zhong-Ping Sun; Chen Yang; Juan Jiang; Lily Wan; Jia-Qi Ai; Yan Wang; Sidiki Coulibaly; Bei-Sha Tang; Jian Wang; Jian-Hong Wang; et al. (Scientific Reports)
Abstract α-Smooth muscle actin (αSMA) is best characterized as the building block of thin filaments in smooth muscle cells. We observed a clear αSMA immunolabeling in adult human hippocampal mossy fibers (MF), prompting us to explore this novel pattern in phylogenic and ontogenic perspectives in the present study. αSMA immunolabeling occurred distinctively at the hippocampal MF terminals in humans from infancy to elderly. Hippocampal MF αSMA immunolabeling was not observed in mice and rats, visible in CA3 in guinea pigs and cats, and prominent in CA3 and dentate hilus in Rhesus monkeys. MF αSMA immunolabeling in human hippocampus emerged and refined from the last gestational trimester to early infancy. A transient overall neuronal labeling of ɑSMA was observed in prenatal human brains. ɑSMA expression was detected in human and rat primary neuronal cultures. The specificity of ɑSMA antibodies was confirmed by ACTA2 small interfering RNA (siRNA) silencing in SH-SY5Y cells. With this validation, we detected a higher αSMA protein level in dentate gyrus lysates relative to other human brain areas. Taken together, αSMA is distinctly expressed in human hippocampal mossy fibers. This pattern is related to hippocampal evolution among mammals and involves a refinement of neuronal αSMA expression during brain development.